An Analysis of the Incidence and Outcomes of Major Versus Minor Neurological Decline After Complex Adult Spinal Deformity Surgery: A Subanalysis of Scoli-RISK-1 Study. Issue 13 (1st July 2018) - Kato, So; Fehlings, Michael G.; Lewis, Stephen J.; Lenke, Lawrence G.; Shaffrey, Christopher I.; Cheung, Kenneth M.C.; Carreon, Leah Y.; Dekutoski, Mark B.; Schwab, Frank J.; Boachie-Adjei, Oheneba; Kebaish, Khaled M.; Ames, Christopher P.; et al.
Abstract : Study Design: A subanalysis from a prospective, multicenter, international cohort study in 15 sites (Scoli-RISK-1). Objective: To report detailed information regarding the severity of neurological decline related to complex adult spine deformity (ASD) surgery and to examine outcomes based on severity. Summary of Background Data: Postoperative neurological decline after ASD surgeries can occur due to nerve root(s) or spinal cord dysfunction. The impact of decline and the pattern of recovery may be related to the anatomic location and the severity of the injury. Methods: An investigation of 272 prospectively enrolled complex ASD surgical patients with neurological status measured by American Spinal Injury Association Lower Extremity Motor Scores (LEMS) was undertaken. Postoperative neurological decline was categorized into "major" (≥5 points loss) versus "minor" (<5 points loss) deficits. Timing and extent of recovery in LEMS were investigated for each group. Results: Among the 265 patients with LEMS available at discharge, 61 patients (23%) had neurological decline, with 20 (33%) experiencing major decline. Of note, 90% of the patients with major decline had deficits in three or more myotomes. Full recovery was seen in 24% at 6 weeks and increased to 65% at 6 months. However, 34% continued to experience some neurological decline at 24 months, with 6% demonstrating no improvement. Of 41 patients (67%) with minor decline, 73% had deficits in one or two myotomes. Full recovery was seen in 49% at 6 weeks and increased to 70% at 6 months. Of note, 26% had persistence of some neurological deficit at 24 months, with 18% demonstrating no recovery. Conclusion: In patients undergoing complex ASD correction, a rate of postoperative neurological decline of 23% was noted with 33% of these being "major." Although most patients showed substantial recovery by 6 months, approximately one-third continued to experience neurological dysfunction. Level of Evidence: 2